MANAGEMENT OF FOREST SOILS CONSIDERING WATER EROSION AS A CONTROL FACTOR - Coutinho, M A; Antunes, C R (Desertification in the Mediterranean Region a Security Issue)
In Mediterranean regions, water erosion is strongly linked to desertification and relates mainly to constraints of land use. Soil and water play very important roles as production factors in agriculture and forest crops, so they are of almost importance in the management of forest soils for sustainable productivity. The density of plants, the amount of water available and the soil properties are aspects to take in account in the management of forestlands. The lower stage canopies of bushes and herbs established in forest lands compete for water with the trees, but are important in the maintenance of ecosystems and absorbing the energy of rainfall and throughfall, thus reducing soil erosion. For the assessment of the available water and the rainfall erosion it is necessary to know the hydrologic behaviour of tree canopies and, mainly, the role of the leaves. The major aim of this study is to present and analyse the role of the leaves in what concerns canopy interception, retention and throughfall and to present values for the leaves' retention and throughfall erosivity, obtained experimentally. Typical conditions, in Southern Portugal, are presented for mixed stands of cork and evergreen oaks, with cereals or pasture covers, and for eucalyptus. Proper management attitudes are necessary to ensure productivity, environment stability (i.e. avoiding desertification) and, consequently, improve homeland and global security.
Keywords: erosion; forest management (voyant); rainfall interception; retention; throughfall; vegetation canopies; water

THE CHALLENGES OF LAND AND WATER RESOURCES DEGRADATION IN JORDAN : DIAGNOSIS AND SOLUTIONS - Abu-Sharar (Desertification in the Mediterranean Region a Security Issue, 2014)
Desertification is the loss of complexity of biological and/or economic productivity of crop-, range- or wood-lands. Reasons of such a loss is mainly due to climatic change and unsustainable human activities. The arid and semi-arid lands of Jordan are sensitive to human interference that resulted in a severe depletion of its natural resources and in different forms of land degradation due to multiple interaction of socio-economic factors. Further, degradation will continue if human activities are not carefully controlled and managed. Almost 90% of the land area of Jordan receives less than 200 mm of rainfall annually. This is reflected in poor structural stability of soils and the subsequent vulnerability to excessive erosion following shallow rainstorm events. Such a fragile ecosystem has also been manifested by non sustainable land use patterns and poor vegetative cover of the range land and the remaining forest batchs. Therefore, most of the economic activities take place on the remaining 10% of the land area and the competition between different user groups for these lands is, therefore, intense. Factors such as livestock and grazing practices, inappropriate agricultural and irrigation techniques, the marginalizing of lands, poor socio-economic conditions and a high population growth rate as well as weak institutional arrangements need to be considered in a comprehensive and integrated framework. Rangelands are deteriorating at an accelerated rate due to widespread overgrazing, uncontrolled herd movements, firewood collection, unsuitable cultivation practices, and persisted periodic droughts, all of which worsen ecological conditions. Cultivation of marginal lands, and unsound practices such as ploughing down slopes, and use of heavy farm machinery have accelerated rate of soil erosion and lowered land productivity. Urbanisation is also steadily encroaching onto good quality agricultural land in the higher rainfall areas of the Jordanian highlands, reducing the traditional production areas of food crops such as wheat and barley. Jordan suffers from a scarcity of water resources, which is compounded by poor management of existing supplies. Pumping of aquifers for irrigation and municipal uses has been exceeding their renewable safe yield. No serious attempts have been committed to improve natural recharge into these aquifers, encourage water harvesting practices or adopt water conservation measures, especially in irrigation. The current demand for municipal, industrial and agricultural water in Jordan exceeds sustainable water supply and the problem is further aggravated in dry winters like the case in the 1998/99 season. Irrigation has made crop production possible in many areas but the long-term effects of fertilizers and pesticides on water quality, as well as on soil salinity, have been given only limited attention. Furthermore, poor wastewater treatment, and industrial pollution have compounded the problem. Current and future deterioration of water quality will have marked effects on land degradation. Socio-economic factors contribute negatively to desertification and to efforts to combat its effects, poverty constitutes a vicious circle linking deterioration of natural resources to deterioration of livelihoods. Also, the population increase is adding an additional pressure to land and water resources, as people need to encroach further on fragile soils, sparse vegetation and limited water resources. The institutional capabilities of the Government as well as the existing legislation and policies need to address the serious degradation of its agricultural, range and forest lands, and aim to improve land capabilities and increase production for communities will require support. Financial and technical support will be required to introduce new agricultural products, agricultural techniques, water harvesting techniques that will result in increased land productivity, yet with less pressure on fertility and water resources. Also, communities will be encouraged to engage in diversified economic activities that will alleviate pressure on natural resources. This may be accomplished through the adoption of participatory approaches that raise awareness of local communities to threats of desertification and to strengthen local institutions, which are essential for reversing desertification and environmental degradation, especially considering Jordan’s transition economy.
Keywords: Agriculture; degradation; desertification; Jordan; management (voyant); resources; water

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Juvenile–adult tree associations in a continental Mediterranean ecosystem: no evidence for sustained and general facilitation at increased aridity - Granda, Elena; Escudero, Adrián; de la Cruz, Marcelino; Valladares, Fernando (Journal of Vegetation Science, 2012)
Question How do tree species identity, microhabitat and water availability affect inter- and intra-specific interactions between juvenile and adult woody plants? Location Continental Mediterranean forests in Alto Tajo Natural Park, Guadalajara, Spain. Methods A total of 2066 juveniles and adults of four co-occurring tree species were mapped in 17 plots. The frequency of juveniles at different microhabitats and water availability levels was analysed using log-linear models. We used nearest-neighbour contingency table analysis of spatial segregation and J-functions to describe the spatial patterns. Results We found a complex spatial pattern that varied according to species identity and microhabitat. Recruitment was more frequent in gaps for Quercus ilex, while the other three species recruited preferentially under shrubs or trees depending on the water availability level. Juveniles were not spatially associated to conspecific adults, experiencing segregation from them in many cases. Spatial associations, both positive and negative, were more common at higher water availability levels. Conclusions Our results do not agree with expectations from the stress-gradient hypothesis, suggesting that positive interactions do not increase in importance with increasing aridity in the study ecosystem. Regeneration patterns are species-specific and depend on microhabitat characteristics and dispersal strategies. In general, juveniles do not look for conspecific adult protection. This work contributes to the understanding of species co-existence, proving the importance of considering a multispecies approach at several plots to overcome limitations of simple pair-wise comparisons in a limited number of sites.
Keywords: faginea; Juniperus thurifera; patterns; Pinus nigra; Quercus; Quercus faginea; Quercus ilex; Regeneration; spatial; spatial patterns; Stress-gradient hypothesis; water; Water availability

Adsorption equilibria of water vapor on cork. - Lequin, Sonia; Chassagne, David; Karbowiak, Thomas; Gougeon, Régis; Brachais, Laurent; Bellat, Jean-Pierre (Journal of agricultural and food chemistry, 2010)
We report here for the first time a complete thermodynamic study of water vapor adsorption on crude cork powder and plate. Adsorption-desorption isotherms were accurately measured by thermogravimetry at 283, 298, and 313 K in a large range of relative pressure. Adsorption enthalpies were determined by calorimetry as a function of loading. Adsorption-desorption isotherms exhibit a hysteresis due to the swelling of the material. The influence of the presence of lenticels on the adsorption properties of cork is found to be negligible. A detailed analysis and interpretation of adsorption data allow proposal of an adsorption mechanism in two steps. (i) First, water adsorbs on hydrophilic sites constituted by hydroxyl and methoxyl groups. (ii) Then water adsorption continues by clusters formation around the hydrophilic sites.
The following values have no corresponding Zotero field: accession-num: 20192215
Keywords: Adsorption; Plant Bark; Plant Bark: chemistry; Quercus; Quercus: chemistry; Thermodynamics; water; Water: chemistry

Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Penuelas, Josep; Lope-Piedrafita, Silvia (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )
Keywords: Droughts; Magnetic Resonance Imaging; Physiological; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus: metabolism; Seedling; Seedling: metabolism; Soil; Soil: analysis; Stress; Time Factors; water; Water: metabolism (citation)

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree Physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population’s ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (Amax), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased Amax and increased iWUE, and cold reduced Amax and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.
10.1093/treephys/tpn007
Keywords: Adaptation; Biological; Biological: physiology; Cold Temperature; Droughts; eﬃciency; Freezing; Genetic Variation; Hot Temperature; Nuts; photosynthesis; Photosynthesis: physiology; Physiological; Quercus; Quercus ilex; Quercus: physiology; Stress; thermal tolerance; Trees; water; water use; Water: physiology

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl237
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Parent material effects on Mediterranean woodland ecosystems in NE Spain - Kooijman, A M; Jongejans, J; Sevink, J (Catena, 2005)
A field survey of an evergreen Mediterranean woodland area in NE Spain on three silica-rich parent materials (granite, granodiorite and schist) was used to test whether parent material had a separate effect on ecosystem functioning in addition to aspect and position on the slope. As expected, vegetation was taller and denser on north-facing slopes and/or lower slope positions. However, parent material appeared to have additional effects, with significant increases in tree height, tree cover, shrub height and ratio of woodland to maquis vegetation from granite towards granodiorite and schist. There was also a parallel increase in mull humus forms, indicating increasing litter breakdown. The lower productivity on granite may be partly attributed to drought stress, as indicated by the greater proportion of shallow soils and the sandy to loamy sand texture. However, nutrient stress may be equally important. Plant N/P ratios were significantly greater on granite, and plant and soil P contents were less than on the other parent materials, suggesting that P-availability was limited on granite. The greater productivity of soils on schist than on granodiorite may reflect less severe drought stress because of their finer texture. These results suggest that parent material is an important factor regulating productivity in Mediterranean ecosystems through varying drought stress and availability of nutrients.
Keywords: biomass; Drought stress; nitrogen; Nutrient; phosphorus; Soil; Vegetation; water

Cryopreservation of Quercus suber and Quercus ilex embryonic axes: in vitro culture, desiccation and cooling factors. - Gonzalez-Benito, M Elena; Prieto, Roberto-Moreno; Herradon, Esther; Martin, Carmen (Cryo letters, 2002)
This study examines different factors included in the cryopreservation protocols for Quercus ilex and Q. suber embryonic axes. In vitro incubation temperature played an important role in the appropriate development of Q. ilex axes, as 15 degrees C was superior to 25 degrees C. Q. suber axes proved to be more sensitive to desiccation and cooling. Poor survival (35%) was observed when axes were included into cryovials and then in liquid nitrogen, and none when immersed in sub-cooled liquid nitrogen (-210 degrees C). Q. ilex axes showed poorly organised development in vitro (c. 50% of non-cooled axes showed shoot development). However, c. 80% survival was observed after cryopreservation (either in liquid nitrogen or sub-cooled liquid nitrogen at 0.34 g water / g dry weight), of which c. 15% showed shoot development.
Keywords: Cryopreservation; Cryopreservation: methods; Cryoprotective Agents; Cryoprotective Agents: pharmacology; Culture Techniques; Culture Techniques: methods; Desiccation; Desiccation: methods; embryonic axes; germination; germination temperature; Germination: drug effects; liquid nitrogen; plantlet development; Quercus; Quercus: embryology; Seeds; Seeds: chemistry; Seeds: embryology; Survival Rate; Temperature; water; Water: analysis

A landscape in transition: an historical perspective on a Spanish latifundist farm - Pérez, A S; Remmers, G G A (Agriculture, ecosystems & environment, 1997)
An agricultural landscape, as a social construction, is not static, but a reflection of the balance of social forces which influence the way in which the natural resources of the site are combined. To understand and evaluate the current configuration of a landscape, and to define and understand criteria according to which a future landscape may be designed, it is necessary to analyse its historical construction. In this paper we follow these steps, taking as a point of reference a farm in one of the most important agricultural regions of Spain, the Guadalquivir river valley in Andalucla. This region stands out for its high production potential, social inequity and environmental degradation. The paper describes global changes in the use of the land in this river valley over the past 3 centuries, and uses aerial photographs from 1956 and 1990 to outline changes on the 1150-ha Los Humosos farm, recently granted to a co-operative of land labourers after years of struggle for land. Through this change in tenure the criteria 'control' and 'distribution of benefits' are achieved. Nine other criteria derived from the historical analysis were used to compare four different farm design scenarios through multi-criteria programming, which was preceded by an assessment of the biogeophysical characteristics of the land. However, this appeared to be insufficient to cope with essential criteria such as landscape architecture and biodiversity, because minor landscape elements were neglected which are important starters for the design of an ecological infrastructure. Water, a problematic resource in Mediterranean agriculture, paradoxically turned out to be an important characteristic of these landscape elements. From historical, ecological and social perspectives, new proposals for farm landscape design must necessarily and radically break with the recent past. It appears, however, that to produce agricultural landscapes of quality in the Guadalquivir river valley would involve tough social struggle, that nonetheless is found to use the margins left over by the dominant socio-economic, cultural and political structures. Finally, an agro-ecological option is proposed as a transitional design
Keywords: ecological agriculture; History; land labourers; landscape; Mediterranean; Spain; water

Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua - J.Ma, ESPELTA; RETANA, J; Riba, M (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation
Keywords: Holm oak; light; Regeneration; Seedling; water